Implementation of Digital Storytelling Based on Multicultural Literature for Enhancing Early Childhood Literacy Skills - Rahman, Mohd Nazri Bin Abdul; Malek, Aishah binti Abdul (Procedia of Social Sciences and Humanities, 2024)
Enhancing digital storytelling through multicultural literature is a powerful tool for developing early childhood education's literacy skills. Educators can create immersive experiences that engage young learners from various backgrounds by weaving diverse stories from different cultures into digital platforms. This approach not only fosters a love for reading but also promotes cultural awareness and empathy. In this article, we will explore the significance of incorporating multicultural literature in digital storytelling to enrich the literacy skills of young children, providing them with a holistic and inclusive learning experience. Development This module adapts the Design and Development approach which involves 3 phases namely (i) requirements analysis, (ii) design and development, and (iii) Implementation and Evaluation. Module Implementation and Evaluation is implemented through a Quasi-Experimental approach. The data collection methods used are in-depth interviews, observation, and document analysis. The sources of data are the community involved in the implementation of the Hybrid Learning Module and documents. The collection of research data has been obtained through in-depth interviews and document analysis of children’s work and teaching and learning records of teachers and parents. The interview results were transcribed verbatim, and conclusions were drawn based on thematic analysis. The findings of the study show that the implementation of the digital storytelling has a positive impact on the community involved in aspects of behavior, attitude, and practice, pedagogical competence and skills, learning achievement, interest, and motivation as well as smart teacher-parent sharing.